Decomposition Analysis of Antenatal Care Utilization Inequities in Kembata Tembaro Zone, Southern Ethiopia - Dejene Ermias Mekango; Sisay Moges; Bereket Abrham Lajore; Alula Seyum Buda; Tekle Ejajo; Desta Erkalo (Ubiquity Press, 2023)
Background: Health equity has emerged as a global issue in the post-2015 Sustainable Development Goals, and Ethiopia is no exception. Despite positive improvements, inequities in maternal health service utilization among demographic groups continue to be one of Ethiopia's significant challenges in decreasing maternal mortality. This study focuses on antenatal care service discrimination among a local poor group known as the "golden hands" community in Ethiopia's Kembata Tembaro zone. The subgroup community consists of outcast artesian groups known as "golden hands," formerly known as "Fuga," who face discrimination in all aspects of life owing to their living conditions and ethnic background. Methods: A community-based comparative cross-sectional study was conducted in Ethiopia's Kembata Tembaro, zone in the Southern Nations, Nationalities, and Peoples' Region (SNNPR), from January to February 2022. The study focused on two groups, "golden hands" and "non-golden hands," consisting of women aged 15-49 years. Using stratified and multistage cluster sampling, 1,210 participants were selected, with 440 from golden hand communities and 770 from non-golden hand communities. Data was collected through translated questionnaires, and data quality was rigorously monitored. The concentration curve and index, as well as logistic-based decomposition analysis, were used to examine inequality. The statistical significance threshold was set at p < 0.05 with a 95% confidence interval. Result: This study comprised 1,210 eligible participants, 440 of whom were golden hand community members. Discrimination accounted for 60.23% of the decreased antenatal care (ANC) service use by the golden hand community. Age, urban residence, and wealth index were the most important independent factors with statistically significant contributions to changes owing to differences in effects (discriminated difference). Conclusion: Since ANC service discrimination is prevalent, the government and nongovernmental organizations should take steps to ensure that marginalized groups in society, such as golden hand women, the poor, the uneducated, and rural people, have equal access to service utilization opportunities.